Santa clawed - Brown, Rita Mae (New York : Bantam Books, 2008)
Harry and her husband, Fair, have gone to fetch a Christmas tree at the tree farm run by The Brothers of Love, a semimonastic organization that tends to AIDS patients, when they find the tree they've chosen grimly decorated with a dead body. Can Harry, the sleuthing cats Mrs. Murphy and Pewter, and corgi Tee Tucker save the season from a killjoy who's decided to gift the festive little town of Crozet, Virginia, with murder?
107347
Keywords: Haristeen, Harry (Fictitious character); Murphy, Mrs. (Fictitious character); Women postal service employees; Women detectives; Women cat owners; Cats; Christmas stories; Crozet (Va.); Detective and mystery fiction; Fiction